Quando os alunos já são professores : ressentimento, teoria e prática na experiência do PARFOR - Santos, Marcelo Alexandre dos (2017)
The present work consists of a study about the teacher-student relationship when students are already teachers. The specificities of this relationship are analyzed from two fundamental elements, namely: the resentment dynamics between students and teachers and the taboos about teaching, related to the problem of aversion to the teaching profession. In spite of the approximation to psychology - especially in regard to resentment - the approach employed is philosophical, taking as reference the studies of the Critical Theory of society produced by the first generation theorists of the Frankfurt School, including Theodor Adorno. They are joined by the analysis of other philosophers of modernity, such as Nietzsche and Marx, as well as present-day Frankfurtian intellectuals, such as Zuin, and the philosophy of education in Brazil, especially Saviani. The object of the study presented here is situated historically. Thus, the teacher-student relationship now studied consists of a singular case: a licentiate course in Pedagogy in which students already have the experience of teaching, that is, they are professionals with a practical contribution and familiar with the classroom dynamics. In view of this context, this paper aims to answer the following questions: Does the act of attending a degree in Pedagogy when one already has the experience of teaching practice modify the characteristics of the teacher-student relationship? Would a priori teaching experience contribute to the acceptance of course practices that would enable the formative experience (Erfahrung) (Bildung)? The answers to these questions are produced from the analysis of the highlighted elements in articulation with the controversy of the relation between theory and practice, developed through the application of the negative dialectic method, proper to the Adorno’s Critical Theory. Through the conclusions reached from the answers to these questions, it is possible to better understand the current motivations of the aversion to the teaching profession based on the objective conditions of existence in which it develops in the present days. This whole set of analysis is inserted in the conjunctural dynamics of contemporary capitalist society with the aim of enabling the dialectical articulation between the objective and subjective data gathered in the research. The results show that the fact that the student is already a teacher, in the singular case studied, modifies several aspects of the teacher-student relationship. This change is related, among other elements, to the dissociation between theory and practice which, in these circumstances, underlies the aversion to the teaching profession. In addition, it was possible to verify that the fact that the student is already a teacher does not interpose immediately as an incentive element of practices that provide the formative experience. In this set, it is verified that the current taboos about teaching is reproduced in a specific way when students are already experienced teachers, including the conditions addressed in this research, modifying, even, the characteristics of resentment in the teacher-student relationship that is in this context. Therefore, the present work can contribute to the development of actions that can effectively overcome the objective and subjective determinations that constantly reproduce the resentment, the taboos and the semiformation that pervade the teaching profession.